Correlates and predictors of obesity‐specific quality of life of former participants of a residential intensive lifestyle intervention. (24th March 2018) - Elbe, A.‐M.; Elsborg, P.; Dandanell, S.; Helge, J. W.
Summary: Introduction: The aim of this study was to investigate the relationship between weight loss during and after a unique type of weight loss intervention, namely, a residential intensive lifestyle intervention (ILI), and participants' obesity‐specific health‐related quality of life (HRQOL) several years after the intervention. In the residential ILI under investigation, participants attended a 10‐ to 12‐week long course away from their daily living environment, namely, at Ubberup Folk High School located in Denmark. Methods: A total of 79 former participants (31 male, mean age 36.6; SD = 12.7 years) who had participated in the intervention on average 5.3 (SD = 3.2) years ago were recruited for this study. They completed a questionnaire on weight‐related quality of life (IWQOL‐lite) and physical activity, as well as measurements of VO2 max, blood pressure, Homeostatic Model Assessment for Insulin Resistance, waist circumference and hand grip strength. Results: The study results showed that weight change after the end of the intervention could predict HRQOL whereas how much weight they lost during the intervention could not. Furthermore, almost all of the investigated physiological factors were related to participants' current HRQOL. Waist circumference showed relationships with four of the five aspects of HRQOL. Conclusion: Focusing on behavioural change, adhering to improved lifestyle and maintaining weight loss after the end of the intervention seem to be the key not only for cardio‐metabolic risk factors but also for sustainable HRQOL.